Pequenos gestos de afeto: as implicações de si no documentário contemporâneo produzido no Ceará - Paula, Janaina Braga de (2013)
The research focuses on part of the documentary produced in Ceará, in the last decade, whose director life is at the center of the scene. Elected as a privileged field of analysis, three significant films of this recent production: Casa da vovó, Cidade Desterro and Supermemórias. In common, the films deal with aspects of the lives of filmmakers, however, each in its own way, is able to mobilise unique reflections that problematize the documentary field: the dilution of boundaries between subject and object, the dialogue with the contemporary visual arts, the relationship with the city, the essayistic character, more fluid narrative as oppose a sensorimotor model, learning process that is tied to the arts. This is not a production sample of Ceara, but some artists chosen work that potentially stimulate a fruitful thinking about life and work, subjective processes, memory composition, affections.